ANALISIS BUTIR SOAL MATERI GEOMETRI KELAS V SD - Atika Anggraini; Regina Misyah Aylia; Jesi Alexander Alim (Universitas Muhammadiyah Makassar, 2022)
This research is a descriptive research that aims to determine the quality of the items in the mathematics subject subject Geometry students at SDN 012 Tambak. The subjects in this study were practice questions in class V mathematics. The data from this research were obtained by collecting data in the form of daily math practice questions and answer sheets for class V students. The data analysis technique was quantitative descriptive data analysis. Based on the results of data analysis, in terms of content validity it is a valid item because it has rcount greater than rtabel at a significant level of 5%, in terms of overall reliability it is reliable with a distribution of 4 items of moderate reliability and 1 item of high reliability, in terms of difficulty level has a disproportionate distribution of difficulty level comparisons because there are more easy questions than moderate questions and there are no difficult items so that they are not in accordance with the comparison between easy-medium-difficult questions, and in terms of discriminating power most of them have discriminating power very good item.